Prognostic evaluation of the norepinephrine equivalent score and the vasoactive-inotropic score in patients with sepsis and septic shock: a retrospective cohort study - Li, Wenzhe; Wang, Yi; Abuduaini, Buzukela; Li, Xiang; Pan, Pengfei; Cui, Jian; Yu, Xiangyou (Frontiers in Cardiovascular Medicine, 2024)
Background: This study investigated the association between vasoactive medication exposure and mortality risk in patients with sepsis using the norepinephrine equivalent score (NEE) and vasoactive-inotropic score (VIS).Methods: This retrospective cohort study included adult patients with sepsis requiring vasoactive agents. The data were extracted from the MIMIC-IV database. The primary outcome was the 28day mortality. Multivariate Cox regression was used to elucidate the relationship between vasoactive medication exposure and 28-day mortality, as quantified by VIS and NEE. Hazard ratios (HR) with 95% confidence intervals (CI) for 28-day mortality were generated, and forest charts were generated to present the results of univariate and multivariate analyses. The Kaplan-Meier method was used to analyze the cumulative incidence of the 28-day mortality. A nomogram was constructed to predict the prognosis of patients with sepsis.The present study encompassed 9032 patients diagnosed with sepsis who received vasoactive therapy, of which 4229 patients were further analyzed at the second hour after the onset of sepsis. Distinct variations in demographic data were observed between survivors (n = 3265, 77.21%) and non-survivors (n = 964, 22.79%). Multivariate analysis indicated that several factors, including VIS > 15.04 (p = 0.001), NEE > 0.10 (p <0.001), heart rate (p = 0.045), mean arterial pressure (p = 0.009), respiratory rate (p <0.001), oxygen saturation (p <0.001), blood urea nitrogen (BUN) (p = 0.001) and Acute Physiology and Chronic Health Evaluation II (p <0.001) were significantly associated with 28-day mortality in the patients with sepsis. The NEE score, respiratory rate, SpO2, and BUN were incorporated into the nomogram model with a concordance index of 0.779 and an AUC of 0.802 (95% CI 0.787-0.818).We found that both VIS and NEE had favorable values for predicting mortality risk in patients with sepsis in the intensive care units. VIS and NEE in the second hour after sepsis onset were independently associated with 28-day mortality in patients with sepsis.